Kejadian Anemia Pada Ibu Hamil Trimester I Terhadap Status Hiperemesis Gravidarum Di Wilayah Kerja PKM Bambu - Susanti, Susanti; Parwati, Dewi; Musdalifah, Musdalifah; Irma, Irma (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2022)
Anemia is a disease that can occur during pregnancy due to the mother's iron deficiency. Mothers who have insufficient knowledge about the benefits of iron will show behavior that is not as recommended, so complete information about the benefits of iron is needed. Hyperemesis gravidarum can cause disruption to daily activities, thereby endangering the health of the fetus and mother, and can even cause death. 6. Apart from that, nausea and vomiting also have a negative impact on pregnant women, often occurring in the morning, and can even occur at any time or sometimes occur at night. 40-60% of these symptoms usually occur in multigravidas. The aim of this PKM is to determine the relationship between nutritional status and hyperemesis gravidarum with the incidence of anemia in pregnant women in the first trimester at PKM Bambu. The service method begins with educational activities carried out by providing material, symptoms and preventing anemia in pregnant women. Providing education about anemia provides an initial understanding of the impact of anemia. The second activity was carried out after providing education by carrying out early detection of anemia through Hb examination. The third activity is nutritional counseling which will be provided by a nutritional counselor. Sampling used a total sampling technique, namely a sampling technique whose number was the same as the population with a sample size of 30 respondents. Based on the results of a questionnaire that was carried out on 30 pregnant women in the first trimester who experienced anemia at PKM Bambu, some data was obtained about the characteristics of respondents based on age and employment status. There is a positive relationship between X1 (nutritional status) and Y (the incidence of anemia in pregnant women) and it is statistically significant.